Joao Antonio - the emerging writer in Malagueta, Perus and Bacanaco - Machado, Guacira Marcondes [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2024)
At the beginning of the 20th century, the country witnessed a rural exodus that increased the problems of the cities. All of this served as a source of inspiration for the literary world, which sought to raise awareness of the injustices and lack of interest shown to that portion of the poor population, made up of marginalized working classes, who were the result of this rural exodus to the cities. Joao Antonio (1937-1996) would later become known, after the publication of his first book, Malagueta, Perus and Bacanaco (1963), among the so-called peripheral writers, and aimed to take on the role of speaking, producing his own discourse, in a confessional tone, which he developed after being born in the outskirts of Sao Paulo, in Presidente Altino. In this paper, we analyze one of the short stories from the award-winning first book, Malagueta, entitled Busca (Search). In a brief text, we will pinpoint how Joao Antonio uses the procedures of a hybrid genre, called recit poetique [poetic narrative] by the French author Jean-Yves Tadie, from which we recognize the project of literary creation emerging at this initial moment of the production of his discourse, in a confessional tone that will remain one of his traits.
Keywords: Joao Antonio; Busca; Poetic narrative; Poetic short story